Transcription factor TCF3 promotes bladder cancer development via TMBIM6-Ca2+-dependent ferroptosis - Wei-Feng Yang; Wei-Ming Guo; Qing-Tian Luo; Jingfen Lu; Zhou-Ke Tan; Yuan-Chun Ye; Gang Fan (Cell Death Discovery)
Abstract TMBIM6, a Ca2+ channel-like protein, shows an increased expression in numerous types of cancer. However, no study has reported its role in bladder cancer. This study aimed to explore the roles and mechanisms of TMBIM6 in bladder cancer. TMBIM6, ferroptosis-related proteins (GPX4, SLC7A11, and FTH1), and calmodulin (CaM) expressions in bladder cancer and paracancerous tissues were obtained by immunohistochemistry. The bladder cells were overexpressed or silenced with TCF3/TMBIM6 with ferroptosis inducer (Erastin)/Ca2+ blocker (BAPTA-AM) to investigate the effects on Ca2+-dependent ferroptosis and other functions. Finally, tumorigenicity was validated in nude mice. TMBIM6 and ferroptosis-related proteins were up-regulated in bladder cancer tissues, but CaM was downregulated. TMBIM6 overexpression enhanced proliferation, invasion, migration, GSH/GPX4 levels, and ferroptosis resistance while suppressing MDA, Fe²⁺, and lipid ROS in bladder cancer cells, effects reversed by Erastin. TCF3 was up-regulated in cancer and enriched in Ca2+ and ferroptosis-related pathways. TCF3 directly interacted with TMBIM6 and transcriptionally activated TMBIM6 expression. Both TCF3 and TMBIM6 overexpression exhibited comparable effects in modulating ferroptosis and other cellular processes, whereas TMBIM6 knockdown effectively reversed these phenotypic alterations. In addition, silencing TCF3 upregulated Ca2+ and CAM levels, while BAPTA-AM reversed these changes. In vivo, ov-TCF3 promoted tumor volume, weight, and TMBIM6 expression, and inhibited Ca2+ concentration, while Erastin reversed these changes. Our findings demonstrate that TCF3 facilitates bladder cancer progression through the enhancement of TMBIM6-Ca2+-mediated ferroptosis resistance. Both TCF3 and TMBIM6 emerge as promising biomarkers and therapeutic targets for bladder cancer intervention.